Mixed mode I/III fatigue behaviour of Polyetheretherketone - Arbeiter, Florian J.; Gosch, Anja; Vojtek, Tomáš; Pinter, Gerald; Hutař, Pavel; Berer, Michael (Elsevier, 2025)
In this work, the fatigue behaviour of Polyetheretherketone (PEEK) under tensile (mode I) and out of plane shear (mode III) loading was examined by using razor blade notched cylindrical bars. By varying the applied mode I and mode III loadings, fatigue fracture curves of pure mode I and mixed mode I/III were established. The aim was to find a suitable method to describe the behaviour of both pure mode I and mixed mode I/III loading via a singular equivalent stress intensity factor. This was found possible by increasing the coefficient of the mode III contribution by more than 500 % compared to previous work on other thermoplastic materials. This significant change of the mode III contribution was mainly attributed to the different thermo-mechanical state of PEEK at the testing temperature of 23 degrees C, as well as the good friction properties of PEEK which leads to a transferal of mode III contributions to mode I contributions due to crack flank sliding of the formed factory roof formations on the fracture surfaces.

In this work, the fatigue behaviour of Polyetheretherketone (PEEK) under tensile (mode I) and out of plane shear (mode III) loading was examined by using razor blade notched cylindrical bars. By varying the applied mode I and mode III loadings, fatigue fracture curves of pure mode I and mixed mode I/III were established. The aim was to find a suitable method to describe the behaviour of both pure mode I and mixed mode I/III loading via a singular equivalent stress intensity factor. This was found possible by increasing the coefficient of the mode III contribution by more than 500 % compared to previous work on other thermoplastic materials. This significant change of the mode III contribution was mainly attributed to the different thermo-mechanical state of PEEK at the testing temperature of 23 degrees C, as well as the good friction properties of PEEK which leads to a transferal of mode III contributions to mode I contributions due to crack flank sliding of the formed factory roof formations on the fracture surfaces.
Mixed mode I/III fatigue behaviour of Polyetheretherketone
Keywords: Mixed Mode I/III fatigue loading; Fracture surface analysis; Equivalent stress intensity factor; Polymer; Mixed Mode I/III fatigue loading; Fracture surface analysis; Equivalent stress intensity factor; Polymer